Individual variables that influence attitudes toward immigrants in schools - León del Barco, Benito; Felipe Castaño, Elena; Gómez Carroza, Teresa (Anales de Psicología / Annals of Psychology, 2010)
In researching what individual determines of the development of prejudiced attitudes, stereotypes, the authoritarian personality, namely right-wing authoritarianism, the dominance orientation social and social anxiety, have been mainly analyzed. In this research we aim to find, through an analysis of structural equation, a model explaining the student attitudes toward immigrants through disruptive behaviour of socialization (social anxiety and social retirement) and the social self-concept of native students. 300 native students participate, aged between 10 and 15 years. We have used the following questionnaires: AFA (Self-concept Form A), BAS-3 (Battery socialization, as a self-assessment) and the Scale of atti-tudes of schoolchildren towards immigrant pupils. The indexes goodness of fit obtained values within the accepted limits and demonstrate that the model provides a good fit. Model results show that most students socially withdrawn and social anxiety scores get lower social self-concept. Finally, the native school with high scores on social self-concept possess more negative attitudes towards their fellow immigrants.